Calculation of Bessel functions by using continued fractions - Valeyev, K. G.; Kostinskii, O. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We propose a new method for the calculation of Bessel functions of the first kind of integral order. By using the Laplace transformation, we solve a linear differential equation that defines the generating function for the Bessel functions expressed in terms of continued fractions.